Inguinal Hernia Mimicking as a Spigelian Hernia. Issue 3 (May 2013) - Tse, PY; Chan, CC; Wong, WM; Cheung, CC
Inguinal hernia is a common surgical condition requiring surgical intervention. The usual clinical presentation is a supra-inguinal swelling with the neck just above and medial to pubic tubercle. We report a case of inguinal hernia in an old lady that presented as an abdominal wall swelling, clinically suggestive of a Spigelian hernia.